Carbon Nanotubes: Short Multiwall Carbon Nanotubes Promote Neuronal Differentiation of PC12 Cells via Up‐Regulation of the Neurotrophin Signaling Pathway (Small 9–10/2013). Issue 9 (16th May 2013) - Meng, Li; Chen, Rui; Jiang, Aihua; Wang, Liming; Wang, Peng; Li, Chen‐zhong; Bai, Ru; Zhao, Yuliang; Autrup, Herman; Chen, Chunying
<x xml:space="preserve">Abstract</x> The front cover image for this special issue was provided by C. Chen and co‐workers. CNTs show good biocompatibility, and can be used to modulate neurite outgrowth in culture and in vivo. Positive effects such as promoting regeneration and differentiation can be initiated by up‐regulating cellular uptake and exocytosis. On page 1786 it is shown that shorter carboxyl‐terminated multiwall carbon nanotubes (MWCNTs) demonstrate higher cellular uptake by PC12 cells and more obvious exocytosis compared to longer ones. Incubation of PC12 cells with carboxylated MWCNTs does not affect cellular morphology or viability at lower concentrations. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>